Bedeutende Sozialutopien im Kontext des deutschen Bauernkrieges und der Lutherischen Reformation: Thomas Müntzer, Michael Gaismair und Johann Hergot - Franz, Anja; Franz, Dietrich-Eckhard (International Dialogues on Education Journal, 2017)
Social-utopian thinking has a long tradition in Germany. Upon closer examination of social-utopian history, it is evident that many society- and utopia-focused critiques point far beyond the then existing social conditions in their declarations and demands. The Reformation and the German Peasants’ War are importnat highlights in this respect. Although all opposing forces derive from the Lutheran critique and programmatic, it is nevertheless first and foremost „bourgeois“ heresy. Martin Luther’s posting of his theses on the door of the castle church in Wittenburg is that famous spark which initiated the Reformation in October 1517, but it is not the only one that critcizes and attacks the Roman-Catholic papacy in the German-speaking area. Through the work of personalities such as Thomas Müntzer, Michael Gaismair or Johann Hergot the Reformation not only spread to all levels of society but it also changed its structure, beginning with religion, to the economy and the sciences, and into education and the arts.